QISHASH LAW AND HUMAN RIGHTS - Rohman, Anas; Setya, Reso Adi; Wahyudi, Wahyudi; Syaifuddin, Muh (Pascasarjana Universitas Wahid hasyim Semarang, 2020)
Abstract The purpose of Islamic criminal law is to preserve the soul, mind, property of society in general, and offspring. Therefore, the position of Islamic criminal law is very important in social life. This is because four of the five objectives of the Shari'a mentioned above can only be achieved by complying with the provisions of Islamic criminal law, and two of them are sequentially with the provisions of Islamic civil law, namely property and offspring, while the mind and soul are solely preserved by the provisions of Islamic criminal law. . The purpose of Islamic criminal law is to preserve the soul, mind, property of the community in general, and offspring. Therefore, the position of Islamic criminal law is very important in social life. This is because four of the five objectives of the Shari'a mentioned above can only be achieved by complying with the provisions of Islamic criminal law, and two of them are sequentially with the provisions of Islamic civil law, namely property and offspring, while the mind and soul are solely preserved by the provisions of Islamic criminal law. . Password : Qishash Law, Human Rights